Application of Jigsaw Type Cooperative Learning as a Form of Application of ANEKA Values ​​in the Teaching and Learning Process - I Wayan Gede Suarjana; Siti Fathimah (Journal Civics And Social Studies, 2021)
The aim of this research is to find out the basic values ​​that lecturers must have and understand as State Civil Servants and to actualize the basic values ​​of ASN through the use of the jigsaw learning method. Through this habituation activity, it is hoped that it can become a benchmark for success in improving public services. There are 6 supporting activities chosen to complete the selected core issue, namely creating and packaging learning plans that focus on student activity. deliver learning material using the Jigsaw type cooperative learning model, compose questions in varied forms, carry out formative evaluations, check student exam/test results, and carry out analysis of student exam/test results. The research findings are that the actualization of ANEKA values ​​that has been implemented has succeeded in motivating and increasing students' understanding and activeness with innovative learning models in the Basic Occupational Health and Safety course. This increase in understanding can be seen from the results of evaluation tests in participating in learning during actualization and increasing student activity during learning time. By analyzing the evaluation results, it was found that students' learning completeness was rated as very good at 35%, good at 50%, and quite good at 15%.